Evaluasi Suplementasi Complete Premix dalam Ransum terhadap Tingkat Kecernaan Kambing Cross Boer - Qisthon, Arif; Suharyati, Sri; Sirat, Muhammad Mirandy Pratama; Liman, Liman (JURNAL KAJIAN VETERINER, 2025)
This study was conducted to apply various concentration levels of complete premix (CP) as a dietary supplement in order to determine the optimal concentration for enhancing nutrient digestibility in Cross Boer goats. The results of this research are expected to provide a scientific basis for developing more effective and efficient feed formulations on farms to accelerate productivity achievement in goats, thereby supporting the Government of Indonesia’s national meat self-sufficiency program and contributing to the realization of food self-reliance as part of the Asta Cita goals. The experiment used 15 male Cross Boer goats aged 8–10 months, arranged in a randomized block design consisting of five treatments with three replications each: basal diet without CP supplementation (P0); basal diet with 0.25% CP (P1); 0.5% CP (P2); 0.75% CP (P3); and 1% CP (P4). The parameters measured were the digestibility coefficients of dry matter (DM), organic matter (OM), crude protein (CP), and crude fiber (CF). Data were analyzed using one-way ANOVA in SPSS version 24, and significant differences (P<0.05) were further examined with Duncan’s multiple range test. The results showed that treatment P1 significantly (P<0.05) affected DM, OM, and CP digestibilities. All treatments had no significant effect (P>0.05) on CF digestibility. Conclusion of this study that supplementation of complete premix up to 0.25% of the total diet could improve nutrient digestibility in Cross Boer goats.